Effects of short-term physical training on the interleukin-15 signalling pathway and glucose tolerance in aged rats - Minuzzi, Luciele Guerra [UNESP]; da Conceição, Luciana Renata; Muñoz, Vitor Rosetto; Vieira, Renan Fudoli Lins; Gaspar, Rafael Calais; da Silva, Adelino S.R.; Cintra, Dennys Esper; Pereira de Moura, Leandro; Ropelle, Eduardo Rochete; Teixeira, Ana Maria; Pauli, José Rodrigo (Elsevier, 2021)
Purpose: Interleukin-15 (IL-15) is a myokine that has been proposed to modulate skeletal muscle and adipose tissue mass, as well as insulin sensitivity. However, the evidence suggesting a role for IL-15 in improving whole-body insulin sensitivity and decreasing adiposity comes mainly from studies using supraphysiological levels of this cytokine. This study examined the effect of a short-term exercise training protocol on the protein content of IL-15, it's signaling pathway, and glucose tolerance in aged rats. Methods: Fourteen Wistar rats were divided into Young Sedentary (Young, n = 4); Old Sedentary (Old, n = 5); Old Exercise (Old.Exe, n = 5) groups. The animals from the exercised group were submitted to a short-term physical exercise protocol for five days. At the end of physical training and after 16 h of the last exercise session, the animals were euthanized, and tissue collection was done. Results: Physical exercise decreased epididymal and mesenteric fat mass and promoted positive effects on glucose tolerance and insulin sensitivity. Muscle IL-15 protein levels were not changed following the short-term physical exercise training with no alterations in the post-exercise IL-15–JAK/STAT signaling pathway. We found a tendency to increased HIF1α and a significant increase in its regulator, PHD2, in the skeletal muscle after exercise. Conclusion: The elderly rats submitted to short-term aerobic physical training did not present skeletal muscle alteration in the protein content of the IL-15 and IL-15-JAK/STAT signaling pathway. However, short-term aerobic physical training was able to modulate the expression of HIF1α and its regulator PHD2, suggesting an essential role of these proteins in improving post-exercise glucose tolerance and insulin sensitivity in elderly rats.
Keywords: Aging; HIF1α; Insulin sensitivity; Interleukin-15; Physical exercise